The observation of rock behaviour in Uniaxial Compression Test (stress-strain curve) granite / Almanabihah Tugiman - Tugiman, Almanabihah (2006)
The Uniaxial Compression Test (UCT) is one of the most common laboratory test undertaken for rock mechanics studies especially to establish the rock strength. This research focuses on the evaluation of physical properties, mechanical properties and engineering properties of granite. The samples of rock were collected from Jabatan Mineral & Geosains Malaysia, which is located at Ipoh Perak. The existing of sample is from Kuala Berang, Terengganu. Twenty samples were prepared for Uniaxial Compression test. For Physical properties test, ten lumps of granite were used to determine specific gravity, porosity and moisture content. From physical properties test, the result of moisture content, for granite is 0.21 %, the value of the density for granite is between 2.7g/cm3 to 3.0g/cm3, specific gravity for granite is 2.95 and for porosity, the result gives is 0.92 % which can be classified as very low percentage o f porosity according to (Anon, 1979). From laboratory performance the uniaxial compressive strength for all samples are 104.8 MPa to 200.9 MPa which can be classified as very strong rock. For the behavior o f the granite, twelve behave in Elastic manner as load was applied to the material, six behave in Elastic - Plastic manner and another two behave in Plastic - Elastic manner. The mode o f failure for the sample in this test is in multiple shear. From correlation value, it shows that there is a low degree o f positive correlation between the two variables. Therefore, it can be concluded that there is no relationship between Young’s Modulus and Uniaxial Compressive Strength, and no relationship between Poisson’s Ratio and Uniaxial Compressive Strength for the testing sample.